International female students' experiences of navigating the Canadian health care system in a small town setting. Issue 5 (2nd September 2016) - Burgess (Munich), K.; McKenzie, W.; Fehr, F.
Abstract: This pilot study explored the international female (IF) students' ( n = 17) lived experiences of health care accessibility while studying in a small town in Canada. Analysis guided by a phenomenological method resulted in three major themes – (1) after arriving to attend university, IF students experienced challenges in staying healthy, such as learning how Canadian medical insurance works and how to access medical help, (2) IF students developed a support system over time, consisting of their university's student advisors, host families and friends and (3) as IF students became familiar with living in Canada, they developed self-directed care strategies such as taking care of each other if they became sick. They also became comfortable reaching out through social media to ask questions and connect with others who were also new to Canada. Recommendations included providing (1) alternative times for IF students to access medical care on campus, (2) a fund where IF students could borrow the upfront costs to see a doctor and (3) health care knowledge dissemination through various media throughout the school year. The outcomes of this study are generally encouraging and may assist IF students to make effective health care decisions while in Canada resulting in a less stressful academic experience.